Ten thousand democracies : politics and public opinion in America's school districts - Berkman, Michael B., 1960- (American governance and public policy., 2005)
The essence of democracy is popular sovereignty. The people rule. In the United States, citizens exercise this right through elected officials that they believe will best represent their own values and interests. But are those interests and values always being followed? Authors Michael B. Berkman and Eric Plutzer provide the first systematic examination of the extent to which the governments closest to the American public-its 10,000-plus local school boards-respond to the wishes of the majority. Ten Thousand Democracies begins with a look at educational reforms from the Progressive era in the late 19th and early 20th centuries through the civil rights movement and ending with Pennsylvania's 2004 tax relief measure. Berkman and Plutzer explore what factors determine education spending levels in school districts, including the effects of public opinion, the nature of local political institutions, and the roles played by special interests. The authors show how board members are selected, how well the boards represent minorities, whether the public can bypass the board through referenda, and how the schools are financed. By providing an innovative statistical portrait that combines public opinion data with Census data for these school districts, the authors answer questions central to democratic control of our schools: how responsive are school boards to their public and when? How powerful are such special interests such as teachers' unions and senior citizens? By using the lens of America's public school districts to examine the workings of democracy, Ten Thousand Democracies offers new insight not only into the forces shaping local education policy but also how democratic institutions may function throughout all levels of government.